Langkap Crunch / Muhammad Akim Hassan - Hassan, Muhammad Akim (2021)
Langkap Crunch (LC) is a sole proprietorship company that has been established by myself, Muhammad Akim bin Hassan as a way to provide scrumptious dessert at an affordable price. The reasoning behind its name is that Langkap is the hometown of the owner and Crunch to signify that the focused product would mainly be scrumptious desserts. LC currently is fully operated by the owner as it is still at a small business and has limited prowess to catch up with larger demand. As of now, there is only one product that has been launched which is mini coco crunch bathe with white chocolate to make a tasty dessert that will surely leave tester with a sense of satisfaction. This premium dessert is done at small batch and it people can purchase this dessert through its Facebook page; Langkap Crunch.